Pengaruh Interest And Financing Charges Terhadap Net Income - Nurlaela Nurlaela; Aryati Arfah; Baharuddin Semmaila; Arifin Arifin (Jurnal Mirai Management, 2022)
Abstract This study aims to determine the effect of Interest and Financing Charges on Net Income at PT.BFI Finance Indonesia, Tbk. Listed on the Indonesia Stock Exchange. The type of data used is qualitative data and quantitative data and the source of the data used in this research is secondary data. Secondary data is data obtained from existing sources which are written data related to financial reports at PT.BFI Finance Indonesia, Tbk. Listed on the Indonesia Stock Exchange. The method of analysis in this study uses simple linear regression analysis, correlation coefficient, coefficient of determination and T test. The result of this research is interest and financing charges have no significant effect on net income at PT. BFI Finance Indonesia Tbk which is listed on the Indonesia Stock Exchange. Keywords: Interest and financing charges, Net income.